2018
DOI: 10.1155/2018/5804942
|View full text |Cite
|
Sign up to set email alerts
|

Lung Ultrasound Is Accurate for the Diagnosis of High-Altitude Pulmonary Edema: A Prospective Study

Abstract: Objective The aim of this study was to assess the diagnostic accuracy of lung ultrasonography (LUS) for high-altitude pulmonary edema (HAPE). Background LUS has proven to be a reliable tool for the diagnosis of pulmonary diseases, including pneumonia, acute respiratory distress syndrome (ARDS), and pneumothorax. LUS also has potential for the diagnosis of HAPE. However, the actual diagnostic value of LUS for HAPE is still unknown. Our objective was to determine the feasibility of using LUS for the diagnosis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…Chest X-ray and CT are other diagnostic methods that are frequently used for the assessment of pulmonary edema. However, previous studies have suggested that LUS is superior to chest X-ray and comparable to chest CT scan for diagnosing pulmonary edema [3,8]. Therefore, we decided not to use these modalities as a reference standard and only included a sensitivity analysis of chest X-ray.…”
Section: Limitationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Chest X-ray and CT are other diagnostic methods that are frequently used for the assessment of pulmonary edema. However, previous studies have suggested that LUS is superior to chest X-ray and comparable to chest CT scan for diagnosing pulmonary edema [3,8]. Therefore, we decided not to use these modalities as a reference standard and only included a sensitivity analysis of chest X-ray.…”
Section: Limitationsmentioning
confidence: 99%
“…An increasing body of evidence supports the use of LUS in diagnosing pulmonary edema and/or pneumonia [5]. Several studies have shown the diagnostic value of LUS in patients with dyspnea or specific diagnoses, such as pneumothorax, high-altitude pulmonary edema, and cardiogenic pulmonary edema [6][7][8][9][10]. LUS has even been suggested to be superior to chest radiography (X-ray) and comparable to chest computed tomography (CT) scan for the diagnosis of pulmonary edema and increased alveolar fluid (commonly referred to as interstitial syndrome) [3,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…EVLW can be assessed by lung ultrasonography, in which it manifests itself as "B-lines", formerly known as "lung comets" [11], first described in patients with pulmonary edema in intensive care units [12][13][14]. In recent times, lung ultrasonography has been increasingly used to assess the development of pulmonary edema at HA, and there is an increasing body of evidence showing that the number of Blines increase during acute exposure to HA [4,5,[15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Correlation between SpO 2 and LUS-verified pulmonary edema has been described in high-altitude edema. 23 "Checkpoint" levels of 90% and 92% for clinical diagnosis of SIPE have previously been suggested. 6,10 Based on our data, choosing a cutoff level below 95% will result in a loss of sensitivity for SIPE diagnosis.…”
Section: Diagnostic Criteriamentioning
confidence: 99%